Non-puerperal mastitis in a Medellin (Colombia) reference center - Bonilla-Sepúlveda, Óscar Alejandro (2020)
Objective: To describe the sociodemographic data, clinical manifestations and treatment in patients diagnosed with non-puerperal mastitis. Methods: Descriptive, retrospective study of medical records in the institutional database between January 1, 2016 and December 31, 2019. Demographic, clinical and treatment data was collected and analyzed using descriptive statistics. Results: The prevalence of nonpuerperal mastitis was 3.8%, in mestizo women about 40.4 years-old at time of diagnosis. The most frequent reason for consultation was inflammatory changes in breast in 84.8% (n = 28), and presence of mass in 12.1% (n = 4). There was association with smoking in 33.3% (n = 11). 97% of the patients received initial treatment with antibiotics (n = 32), and ultrasound-guided drainage was performed in 7 cases (21.2%). No case had drainage by mastotomy, and one patient (9%) was treated with quadrantectomy-type resection. Resolution was obtained in 97% of cases (n = 32) in 4.4 months average, and 7 patients (21.2%) had recurrence. Conclusion: In this study, non-puerperal mastitis affected women in the fourth decade of life with inflammatory changes and pain. Evolution was chronic with episodes of recurrence. Usually the disorder resolved with antibiotics and some needed ultrasound-guided drainage. Up to one third of cases was associated with smoking.